Distinctive Pattern of Cognitive Disorders During Multiple Sclerosis Relapse and Recovery Based on Computerized CANTAB Tests - Natasa Giedraitiene; Gintaras Kaubrys (Frontiers in Neurology, 2019)
Background: Cognition may be affected at least as seriously as physical function during multiple sclerosis (MS) relapse, however MS relapse related cognitive disorders are still underdiagnosed and poorly characterized. The limited number of paper-pencil tests were used for assessment, and nevertheless, some significant changes were found. Unlike the paper-pencil tests, computerized batteries and tests are more sensitive and highly standardized, produce instant scoring and can minimize the learning and practice effects on follow-up. We investigated the cognition during MS relapse with the Cambridge Neuropsychological Test Automated Battery (CANTAB), which has shown sensitivity to cognitive dysfunction across different clinical groups, including patients with MS.Objective: The objective of the study was to assess the cognitive functions with CANTAB battery in MS patients during relapse, in stable MS patients, and healthy controls, and to establish the timing and pattern of cognitive recovery after relapse.Methods: Sixty relapsing, thirty stable MS patients, and thirty controls were assessed with CANTAB. The relapse group was assessed during multiple sclerosis relapse and 1 and 3 months after the first assessment.Results: The score of the difficult task of spatial planning was worse in MS relapse group than in MS stable group (p < 0.05). The scores of medium difficulty tasks of spatial planning, episodic visual recall and working memory were worse in the relapse group than in the control group (p < 0.05), while in stable MS and control groups, the scores of these tasks didn't differ. The most significant improvement of speed of response, spatial planning, episodic visual recall memory and spatial working memory, was established at 1 month after the first assessment, additional improvement of spatial planning and working memory was observed at 3 months after the first assessment.Conclusions: The results of this study indicate that cognitive function is affected during MS relapse. The difficult task of CANTAB battery, which assesses the spatial planning, showed MS relapse related cognitive dysfunction. The changes in scores of episodic visual recall and working memory may be related to MS relapse. A significant improvement in the speed of response, spatial planning, episodic visual recall and working memory was established at 1 month after MS relapse. The additional improvement in spatial planning for the most difficult task and working memory was observed at 3 months after MS relapse. It may be possible that the practice effect had the impact on the improvement of cognitive scores that was noted in relapsing MS patients.